Characterization of N‐methylated amino acids by GC‐MS after ethyl chloroformate derivatization. (15th July 2016) - Reddy, B. Sudarshana; Chary, V. Naresh; Pavankumar, P.; Prabhakar, S.
Abstract : Methylation is an essential metabolic process in the biological systems, and it is significant for several biological reactions in living organisms. Methylated compounds are known to be involved in most of the bodily functions, and some of them serve as biomarkers. Theoretically, all α ‐amino acids can be methylated, and it is possible to encounter them in most animal/plant samples. But the analytical data, especially the mass spectral data, are available only for a few of the methylated amino acids. Thus, it is essential to generate mass spectral data and to develop mass spectrometry methods for the identification of all possible methylated amino acids for future metabolomic studies. In this study, all N ‐methyl and N, N ‐dimethyl amino acids were synthesized by the methylation of α‐amino acids and characterized by a GC‐MS method. The methylated amino acids were derivatized with ethyl chloroformate and analyzed by GC‐MS under EI and methane/CI conditions. The EI mass spectra of ethyl chloroformate derivatives of N ‐methyl (1–18 ) and N, N ‐dimethyl amino acids (19–35 ) showed abundant [M‐COOC2 H5 ] + ions. The fragment ions due to loss of C2 H4, CO2, (CO2  + C2 H4 ) from [M‐COOC2 H5 ] + were of structure indicative for1–18 . The EI spectra of19–35 showed less number of fragment ions when compared with those of1–18 . The side chain group (R) caused specific fragment ions characteristic to its structure. The methane/CI spectra of the studied compounds showed [M + H] + ions to substantiate their molecular weights. The detected EI fragment ions were characteristic of the structure that made easy identification of the studied compounds, including isomeric/isobaric compounds. Fragmentation patterns of the studied compounds (1–35 ) were confirmed by high‐resolution mass spectra data and further substantiated by the data obtained from 13 C2 ‐labeled glycines and N ‐ethoxycarbonyl methoxy esters. The method was applied to human plasma samples for the identification of amino acids and methylated amino acids. Copyright © 2016 John Wiley & Sons, Ltd.